Penerapan Model Pembelajaran Reading, Connecting, Observing, Discussing, Evaluating (ReCODE) untuk Meningkatkan Keterampilan Berpikir Kritis Peserta Didik Kelas VIII SMP IT Nurul Fikri - Rizki Amaliah Afdal; Hasanuddin Hasanuddin; Sitti Saenab (Universitas Negeri Makassar, 2024)
This research aims to 1) knowing the category of critical thinking skills of class VIII students of SMP IT Nurul Fikri before and after being taught with the ReCODE learning model, 2) knowing the magnitude of the increase in critical thinking skills of class VIII students of SMP IT Nurul Fikri after being taught with the ReCODE learning model, 3) knowing the improvement in critical thinking skills of class VIII students of SMP IT Nurul Fikri after being taught the ReCODE learning model, 4) knowing whether there is a similarity in the average critical thinking skills of class VIII students of SMP IT Nurul Fikri who are taught with the ReCODE learning model. This type of research is pre-experimental research with a research design using the One Group Pretest-Posttest Design. school year which consisted of 4 classes with a total of 80 students. The sampling technique uses purposive sampling technique. The research sample consisted of 2 classes, namely class VIII B as an experimental class with 11 students and class VIII D as a replication class with 19 students. The research instrument is a test of critical thinking skills. Data analysis with descriptive and inferential statistics. The results of the analysis show: 1) the score of students' critical thinking skills in class VIII SMP IT Nurul Fikri pretest is in the low category (average score 4.54) while the posttest is in the medium category (average score 11.63) 2) improvement the average N-Gain score for students' critical thinking skills in class VIII SMP IT Nurul Fikri after applying the ReCODE learning model is 0.45 which is in the medium category, 3) there is an increase in the critical thinking skills of students in class VIII SMP IT Nurul Fikri after it is implemented the ReCODE learning model, 4) there is a similarity in the average critical thinking skills of class VIII students of SMP IT Nurul Fikri who are taught using the ReCODE learning model.